1991
DOI: 10.1063/1.460799
|View full text |Cite
|
Sign up to set email alerts
|

The photon-induced reactions of chemisorbed CH3Br on Pt{111}

Abstract: Articles you may be interested inGiessen coupled-channel model for pion-and photon-induced reactions AIP Conf.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…They also proposed that CH 3 possessed the C 3v symmetry in accordance with the evidences observed by the experement 11 in HREELS at 255 K as well as our result.…”
Section: Ch 3 /Pt(111)supporting
confidence: 92%
See 1 more Smart Citation
“…They also proposed that CH 3 possessed the C 3v symmetry in accordance with the evidences observed by the experement 11 in HREELS at 255 K as well as our result.…”
Section: Ch 3 /Pt(111)supporting
confidence: 92%
“…Cryer et al 2 first spectroscopically identified the existence of CH 3 under ultrahigh vaccumn (UHV) conditions on Ni(111) with a combination of a molecular beam technique and high-resolution electron energy spectroscopy (HREELS). The CH 3 groups was also identified on Pd(111) 8 using SIMS and XPS, Fe(100) 9 by temperature-programmed reaction spectroscopy (TPRS) and XPS, and Pt(111) 10,11 surfaces by temperature-programmed desorption (TPD), XPS, reflection adsorption infrared spectroscopy (RAIRS), and HREELS techniques.…”
Section: Introductionmentioning
confidence: 99%
“…CH 3 binds less strongly to the top site of Ni( 111) with E ad of −1.57 eV and becomes metastable on the fcc site of Pt(111) with an approximate E ad of ∼−1.33 eV (we can only find this geometry with a loose convergence criterion). The calculated adsorption energies and harmonic frequencies agree well with previous theoretical predictions, 14,16,18,26 although the predicted frequencies are systematically higher than the experimental ones, 14,22,33 due presumably to the intrinsic error in DFT as well as the harmonic approximation used in the theoretical calculations. Note that Gutieŕrez-Gonzaĺez et al 14 have applied vdW-corrected functionals to study CH 3 adsorbed on Pt surfaces and found similar site preference and site-specific vibrational frequencies as using PBE.…”
supporting
confidence: 83%
“…This is in broad agreement with the PBE results of Nave and Jackson, 26 and the predicted site preference agrees well with the experimental assignments. 23,33 In both cases, the methyl adsorbate forms a pyramidal configuration and bonds with the metal surface with its carbon end. CH 3 binds less strongly to the top site of Ni( 111) with E ad of −1.57 eV and becomes metastable on the fcc site of Pt(111) with an approximate E ad of ∼−1.33 eV (we can only find this geometry with a loose convergence criterion).…”
mentioning
confidence: 99%
“…There is a single detectable absorption band in the C-H stretching region at 2885 cm Ϫ1 and no bands detectable in the low wave number region. In this orientation, the symmetric CH 3 ͑ads͒ deformation that has been observed at ϳ1153 cm Ϫ1 in HREELS measurements, 31 should also be symmetry allowed. Our measured intensity is also consistent with existing literature data on this transition.…”
Section: A Methane and Methylmentioning
confidence: 86%